The İnfluence of Political and Psychological Factors on Women’s Right to Education - Guliyeva, Şenay (Journal of the Human and Social Sciences Researchers, 2024)
This descriptive study, which consists of three main headings, focused on the obstacles encountered, proposals of international organizations for solutions and the right of women to education. Social, economic, political, as well as psychological factors influencing this process were analyzed based on the related literature. In the past, men tended to be more educated than women, but in recent decades the gender gap in education has been reversed in most Western countries even in many non-western countries. However, in a number of countries, women are still experiencing difficulties in terms of accessing the facilities for getting education. Among the countries in which this problem is most often observed, some countries stand out in particular. Afghanistan, Pakistan, Congo, Cameron, India, Nepal are among the countries where this problem is more experienced. Based on the collected data, the following main conclusions were identified: a) poverty, b) gender-based stereotypical ideas and approaches, c) cultural values and the lack of education has an impact on the education of women and their involvement in the educational process. Based on these findings the following proposals are recorded: a) Programs on reduction and eradication of poverty should be provided and materials for education should be accessible to women, b) Conducting studies with parents and community adults in society that involve encouraging them to accept equality between men and women according to gender stereotypes, c) Providing countries with basic literacy programs for women, d) Promoting awareness campaign on the importance of women’s education, e) Overcoming barriers to schooling. For elimination of problems in this direction in Turkey, a number of campaigns are implemented with the participation of the Ministry of Education (MoNE), UNICEF, UNESCO, ILO, civil society, media, private sector.
Keywords: Alan Eğitimleri; Kadın; Eğitim; Toplumsal Cinsiyet; Kadınların Eğitimi; Faktörler; Women; Education; Gender; Women’s Education; Factors; Other Fields of Education; 5. Gender equality; 4. Education; 1. No poverty; 10. No inequality; 16. Peace & justice